Harmonizing factor assay-related testing performed in a large laboratory network. Issue 7 (22nd October 2022) - Favaloro, Emmanuel J.; Mohammed, Soma; Vong, Ronny; Chapman, Kent; Swanepoel, Priscilla; Kershaw, Geoffrey; Cai, Nancy; Just, Sarah; Connelly, Lynne; Brighton, Timothy; Pasalic, Leonardo
Abstract : Coagulation factor testing is commonly performed within haemostasis laboratories, either to assess for bleeding disorders, such as haemophilia, or to investigate unexplained prolongation in routine coagulation assays. The aim of this evaluation was to harmonize procedures and normal reference ranges (NRRs) for investigation of coagulation factors on the ACL TOP 50 family of instruments in a large laboratory network. We employed comparative evaluations using newly installed ACL TOPs 550 and 750 and HemosIL reagents vs. existing 'reference' instrumentation and reagents, predominantly Stago and Siemens, as well as assessment of factor sensitivity in routine coagulation assays, prothrombin time (PT) and activated partial thromboplastin time (APTT). Also, establishment of coagulation factor NRRs using normal plasma samples. HemosIL factor assays showed good comparability with the existing reference methods ( R > 0.9). Factor sensitivity for PT and APTT assays were acceptable at around 30 U/dl. NRRs were established and harmonized across the laboratory network. This evaluation of factor testing on ACL TOP 50 Family instruments identified overall acceptable performance using Werfen reagents and enabled harmonization of coagulation factor testing in our large network.